Synthesis, Spectroscopic Characterization, and Biological Evaluation Studies of 5-Bromo-3-(((hydroxy-2-methylquinolin-7-yl)methylene)hydrazono)indolin-2-one and Its Metal (II) Complexes - Kuruba Siddappa; Nabiya Sultana Mayana (Bioinorganic Chemistry and Applications)
The Schiff base ligand 5-bromo-3-(((8-hydroxy-2-methylquinolin-7-yl)methylene)hydrazono)indolin-2-one (BHMQMHI) was prepared via condensation of 5-bromo-3-hydrazonoindolin-2-one and 7-formyl-8-hydroxy-2-methylquinoline and its Co(II), Ni(II), Cu(II), Zn(II), Cd(II), and Hg(II) complexes have been synthesized and characterized by elemental analysis, conductance data, magnetic susceptibility measurements, IR, UV-Vis, mass spectrometry, 1H NMR, ESR, XRD, and thermal studies. By these spectral studies it is found that Co(II), Ni(II), and Cu(II) complexes have exhibited octahedral geometry whereas the Zn(II), Cd(II), and Hg(II) complexes have exhibited tetrahedral geometry. Potentiometric studies have been carried out on complexes of Schiff base (BHMQMHI) with Cu(II), Co(II), and Ni(II). Calvin-Bjerrum pH-titration technique as used by Irving and Rossotti has been applied to determine stability constants in mixed solvents at 25 ± 1°C. The present study reports the protonation constants of this ligand and stability constants of its metal complexes in dioxane-water (50%, v/v) mixtures. Metal-ligand stability constants fall in the order of Cu(II) > Co(II) > Ni(II) which is in agreement with those reported by Irving stability order. The Schiff base (BHMQMHI) and its metal complexes have been screened for their in vitro antibacterial and antifungal activities by minimum inhibitory concentration (MIC) method. The DNA cleavage activities of all the complexes were studied by agarose gel electrophoresis method. In addition, the free ligand along with its complexes has been studied for their antioxidant activity.